2017
DOI: 10.1016/j.trc.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

An optimization model for integrated planning of railway traffic and network maintenance

Abstract: Railway transportation systems are important for society and have many challenging and important planning problems. Train services as well as maintenance of a railway network need to be scheduled efficiently, but have mostly been treated as two separate planning problems. Since these activities are mutually exclusive they must be coordinated and should ideally be planned together. In this paper we present a mixed integer programming model for solving an integrated railway traffic and network maintenance proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…Our problem is slightly different, but clearly suffers from a similar deficiency. In cases with homogenous or very similar train services it is possible to introduce separation constraints (see Lidén and Joborn, 2017) that achieve more realistic plans, but for cases with mixed traffic and varying train costs it is more cumbersome to resolve this issue. Hence, it is necessary to verify whether feasible timetables are possible to achieve, either by using manual reviews or some technical method such as simulation or a timetabling tool.…”
Section: Mathematical and Practical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our problem is slightly different, but clearly suffers from a similar deficiency. In cases with homogenous or very similar train services it is possible to introduce separation constraints (see Lidén and Joborn, 2017) that achieve more realistic plans, but for cases with mixed traffic and varying train costs it is more cumbersome to resolve this issue. Hence, it is necessary to verify whether feasible timetables are possible to achieve, either by using manual reviews or some technical method such as simulation or a timetabling tool.…”
Section: Mathematical and Practical Propertiesmentioning
confidence: 99%
“…Although the monetary volumes cited above indicate a large potential for a more efficient use of maintenance spendings if the coordination with train traffic can be improved, there are few research publications that treat such joint scheduling problems. Lidén and Joborn (2017) presented a macroscopic optimization model for the integrated scheduling of maintenance windows and train services, which was improved and extended with maintenance crew resource considerations in Lidén et al (2018). The methods developed in these previous publications were tested on various theoretical test instances, but were not applied on any practical case, which is the aim of the current work.…”
Section: Introductionmentioning
confidence: 99%
“…The alternative timetable has the minimum deviation from the original timetable. Lidén and Joborn [25] presented a mixedinteger programming model for long term tactical plan, which simultaneously considered train services and railway network maintenances. The experimental results showed that the model could handle large-scale instances.…”
Section: Consideration Of Train Scheduling and Maintenance Plan-mentioning
confidence: 99%
“…24indicates the fact that when SDSA-train arrives at major station , if the maintenance on segment from major station to major station + 1 is being executed, then SDSA-train must select an operation mode (i.e., Mode 1 or Mode 2) as shown in Figure 3. Constraint (25) indicates the fact that when SDSA-train arrives at major station , there is no conflict with the maintenance window, but it will conflict with the maintenance window at major station + 1 if SDSA-train continues to run, which is illustrated in Figure 5. Then SDSAtrain must select Mode 1 or Mode 2, namely, waiting at major station or switching to normal-speed railway corridor.…”
Section: Variables Definitionmentioning
confidence: 99%
“…Rail infrastructure maintenance is so important that it has attracted a lot of attention from both the rail industry and the academic community. Strategic and tactical maintenance planning of railway infrastructures (Su et al, 2017;Xie et al, 2016), rail inspection scheduling (Lannez et al, 2015;Osman et al, 2017;Peng et al, 2013), as well as the coordination of train scheduling and infrastructure maintenance (D'Ariano et al, 2017;Forsgren et al, 2013;Lidén and Joborn, 2017;Luan et al, 2017;Vansteenwegen et al, 2016), have been widely studied in the literature. See Lidén (2015) for a more detailed review of the rail infrastructure maintenance planning problems.…”
Section: Introductionmentioning
confidence: 99%